Effect of gamma iradiated seeds of Jabon Merah (Neolamarckia macrophylla (Wall.) Bosser) to genetic diversity. Issue 1 (1st December 2022) - Larekeng, S H; Qalbi, N; Rachmat, A; Iswanto, I; Restu, M
Abstract: Jabon merah (Neolamarckia macrophylla (Wall.) as one of the potential industrial forest plantations to meet the need for wood that has a moderate level of genetic diversity. This study aims to analyze the morphological and genetic characters and analyze the stability of genes in explants from red jabon seeds induced by gamma rays at doses of 0 gray, 5 gray, 10 gray, 15 gray, 30 gray, 45 gray and 60 gray, 75 gray, 90 gray, 120 gray and 240 gray. The induced seeds were cultured in vitro . The subculture was started with an initialization on MS0 medium and repeatedly cultured. Finally, the LD50 value was determined using curve fit analysis, explant morphological analysis with SPSS, genetic analysis of explants using RAPD markers and SSR/Microsatellite. The DNA analysis with 9 SSR/Microsatellite and RAPD marker primers showed that most of the induction doses produced more fragments than the control.